The Impact of Madrasah Diniyah in Improving The Quality of Islamic Religious Education at State Elementary School 1 Ketro Kebonagung Pacitan - Supatmi; Anip Dwi Saputro; M. Zainal Arif; Ruhima Fatharani (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
This study aims to examine the impact of implementing Madrasah Diniyah on the enhancement of Islamic education quality at SD Negeri 1 Ketro. Madrasah Diniyah, as a non-formal educational institution focusing on Islamic teachings, plays a crucial role in complementing and enriching the religious education curriculum in elementary schools. The research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The findings indicate that Madrasah Diniyah significantly contributes to improving the quality of Islamic education at SD Negeri 1 Ketro. The integr between Madrasah Diniyah activities and formal school education helps students understand and practice Islamic teachings more deeply. Additionally, extracurricular activities organized by Madrasah Diniyah, such as Quran reading training and hadith studies, enhance students' religious knowledge beyond regular school hours. However, the study also identifies some challenges, such as the lack of coordination between the school and Madrasah Diniyah and students' limited time to participate in activities outside school hours. Despite these challenges, the positive outcomes, such as improved religious understanding and character development, highlight the significant role of Madrasah Diniyah in supporting the goals of Islamic education at SD Negeri 1 Ketro.